Neonatal Metabolic Acidosis in the Neonatal Intensive Care Unit: What Are the Genetic Causes? - Ma, Haiyan; Tang, Zezhong; Xiao, Feifan; Li, Long; Li, Yangfang; Tang, Wenyan; Chen, Liping; Kang, Wenqing; Lu, Yulan; Dong, Xinran; Cheng, Guoqiang; Wang, Laishuan; et al. (Frontiers in Pediatrics, 2021)
Neonatal metabolic acidosis (NMA) is a common problem, particularly in critically ill patients in neonatal intensive care units (NICUs). Complex etiologies and atypical clinical signs make diagnosis difficult; thus, it is crucial to investigate the underlying causes of NMA rapidly and provide disorder-specific therapies. Our study aims to provide an overview of the genetic causes of NMA in patients from NICUs. We performed next-generation sequencing (NGS) on neonates with NMA from January 2016 to December 2019. Clinical features, genetic diagnoses, and their effects on clinical interventions were collected for analysis. In the 354 enrolled patients, 131 (37%) received genetic diagnoses, 95 (72.5%) of them were autosomal recessively inherited diseases. Two hundred and fifteen variants spanning 57 genes were classified as pathogenic (P) or likely pathogenic (LP) in 131 patients. The leading cause was metabolic disorders due to 35 genes found in 89 patients (68%). The other 42 NMA patients (32%) with 22 genes had malformations, renal, neuromuscular, and immune-hematological disorders. Seven genes (MMUT, MMACHC, CHD7, NPHS1, OTC, IVD, and PHOX2B) were noted in more than four patients, accounting for 48.9% (64/131) of the identified pathogenic/likely pathogenic variants. Forty-six diagnosed patients with uncorrected NMA were died or gave up. In conclusion, 37% of neonates with metabolic acidosis had genetic disorders. NGS should be considered when investigating the etiology of NMA in NICUs. Based on early molecular diagnoses, valuable treatment options can be provided for some genetic diseases and achieve better outcomes.